Discursive archaeology: constituting knowledge of militant nurses in trade associations - Deybson Borba de Almeida; Gilberto Tadeu Reis da Silva; Genival Fernandes de Freitas; Maria Itayra Padilha; Igor Ferreira Borba de Almeida
ABSTRACT Objective: To analyze the constituting knowledge of militant nurses in trade associations. Method: Historical research, based on the oral history method, with a qualitative approach carried out with 11 nurses who are/were militants for professional issues since the 1980s in the state of Bahia. The data collected through semi-structured interviews were organized in the software n-vivo 10 and analyzed based on dialectical hermeneutics. Results: We identified pedagogical, administrative, public health, sociological, and trade union background knowledge as constituent of militant individuals. Final considerations: The constituting knowledge of militant nurses are inscribed in the Social Sciences, distanced from biomedical knowledge and power, pointing at ways for structuring nursing curricula. We identified the Brazilian Association of Nursing as a space for political formation.